MAXIMIZING TEACHING AND LEARNING PROCESS THROUGH COMPETENCE-BASED TEACHING AS DEMANDED BY CURRICULUM 2013 AT JUNIOR AND SENIOR HIGH SCHOOLS - Jufri Jufri (Universitas Negeri Padang, 2016)
This paper is aimed at discussing how to maximize the teaching and learning process through competence-based teaching as demanded by Curriculum-13 at junior and senior high schools. The reason to choose this topic is based on the current phenomenon developing at schools today. Based on the writer’s observation and experience there are still many teachers who cannot apply the competence-based teaching in the classroom. They are not aware whether in their teachings they have already obtained their teaching objectives or not. The real teaching objective demanded by Curriculum-13 is that the students get competence through the materials given to them at the end of the lesson. In fact, most of teachers just stop teaching and leave the classroom before the students get competence. The teachers just provide the students with knowledge not competence. This reality and facts emerge big problems in our education. The teachers fail to fulfill their duty and in turn this causes the lowering of education quality in this nation. Based on Peraturan Pemerintah Nomor 19 Tahun 2005 tentang Standar Nasional Pendidikan that is already changed by Peraturan Pemerintah Nomor 32 Tahun 2013, it is said that a teacher should follow Standar Proses in his/her teaching. In Standar Proses the teacher should be able to obtain Indikator Pencapaian Kompetensi at the end of his/her teaching. The writer hopes that this paper will help the teachers in this country to solve their problems in teaching English in the coming time.